Mewaspadai Kolesterol Tinggi: Upaya Pengabdian kepada Masyarakat untuk Kesehatan - Torang Siregar; Almira Amir; Suparni; Anita Adinda (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
Non-communicable diseases (NCDs) have become a significant health issue at both national and global levels. The increasing prevalence of NCDs is closely related to dietary habits that include high cholesterol intake. Excessive cholesterol in the body can lead to various complications, such as heart disease, stroke, and hypertension. Therefore, this outreach aims to educate and enhance public knowledge regarding the complications caused by high cholesterol and preventive measures that can be taken. The outreach activities were conducted face-to-face, involving active participation from the participants. The methods used in the outreach included presentations, interactive discussions, and Q&A sessions to ensure better understanding of the topic. Data were collected through pre-tests and post-tests conducted before and after the outreach. Data analysis using the Shapiro-Wilk test showed p < 0.05 for both pre-tests and post-tests, indicating that the data were not normally distributed (P > 0.05). Further analysis using the Wilcoxon test indicated a significant change in participants' knowledge before and after the outreach, with a p-value < 0.05. The results of this outreach are expected to have a positive impact on the public’s knowledge regarding health risks associated with high cholesterol and to encourage individuals to adopt healthier lifestyles. Thus, it is hoped that the prevalence of NCDs can decrease and the community will be more aware of the dangers of high cholesterol.